A General TR-FRET Assay Platform for High-Throughput Screening and Characterizing Inhibitors of Methyl-Lysine Reader Proteins. (July 2019) - Rectenwald, Justin M.; Hardy, P. Brian; Norris-Drouin, Jacqueline L.; Cholensky, Stephanie H.; James, Lindsey I.; Frye, Stephen V.; Pearce, Kenneth H.
Chromatin regulatory complexes localize to specific sites via recognition of posttranslational modifications (PTMs) on N-terminal tails of histone proteins (e.g., methylation, acetylation, and phosphorylation). Molecular recognition of modified histones is mediated by "reader" protein subunits. The recruited complexes govern processes such as gene transcription, DNA replication, and chromatin remodeling. Dysregulation of histone modifications and consequent downstream effects have been associated with a variety of disease states, leading to an interest in developing small-molecule inhibitors of reader proteins. Herein, we describe a generalized time-resolved fluorescence resonance energy transfer (TR-FRET) assay for a panel of methyl-lysine (Kme) reader proteins. These assays are facile, robust, and reproducible. Importantly, this plug-and-play assay can be used for high-throughput screening (HTS) campaigns, generation of structure–activity relationships (SARs), and evaluation of inhibitor selectivity. Successful demonstration of this assay format for compound screening is highlighted with a pilot screen of a focused compound set with CBX2. This assay platform enables the discovery and characterization of chemical probes that can potently and selectively inhibit Kme reader proteins to ultimately accelerate studies of chromatin reader proteins in normal biology and disease states.